Terminologia da serraria tradicional - NEGRÃO, Jairo Negrão (2019)
This paper has as aim to investigate the specialized lexicon used by professionals in the area of traditional sawmill in the county of Abaetetuba-PA. And also to rescue and keep this specificity safe through academic work of terminology of traditional sawmill, accomplished in UFPA (Federal University of Para) in the county of Abaetetuba. Having as theoretical reference the sciences of lexicon jointly with the thinkers who are reference in the field of terminology like: (Rey, 1985, p.159),(Alves, 2011, p.25), (Barbosa, 1991), (Weinrich, 1979, p, 314), (Frubel, 2006, p.62), (Rondeau, 1984, p.1), Maria tereza Cabré (KRIEGER and FINATTO, 2004, p.35), Faulstich (1995) and Barros (2004, p.100) the methodology of this research consisted of going to the field, in which were done the interviews with professionals of the area, in oral way, that resulted the possibility of subtract from the recordings and image captures the terms-entries and the lexicon variations, necessary to the production of a illustrated glossary of the terminology of traditional sawmill.